2013
DOI: 10.1007/jhep09(2013)087
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations in Chromo-Natural Inflation

Abstract: Chromo-Natural Inflation is the first worked example of a model of inflation in which slow-roll inflation is achieved by "magnetic drift" as opposed to Hubble friction.In this work, we give an account of the perturbations at linear order in this model. Our analysis uncovers two novel phenomena. First, the amplitude of scalar curvature perturbations is not directly tied to the shape of the inflationary potential. This allows the theory to violate naïve formulations of the Lyth bound. Second, the tensor sector o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
272
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(284 citation statements)
references
References 110 publications
(173 reference statements)
11
272
1
Order By: Relevance
“…Taken at face value, the original model (5.293) is in conflict with the CMB data [820]: it either predicts a spectral tilt that is too red, overproduces gravitational waves, or both. Nevertheless, it remains interesting to explore whether large Chern-Simons couplings can arise in consistent string compactifications and if models with viable phenomenology can be constructed.…”
Section: Phenomenologymentioning
confidence: 99%
“…Taken at face value, the original model (5.293) is in conflict with the CMB data [820]: it either predicts a spectral tilt that is too red, overproduces gravitational waves, or both. Nevertheless, it remains interesting to explore whether large Chern-Simons couplings can arise in consistent string compactifications and if models with viable phenomenology can be constructed.…”
Section: Phenomenologymentioning
confidence: 99%
“…Unfortunately, it has been recently shown that this mechanism does not generate a sufficient lepton asymmetry without spoiling inflation [28]. Other, more promising examples are inflationary scenarios that contain SU(2) gauge fields with classical vacuum expectation values, such as gauge-flation [29][30][31] and its variants [32,33], chromo-natural inflation (CNI) [34][35][36][37] and its variants [38][39][40], and models that include spectator chromo-natural-like sectors [41][42][43][44]. Gravitational leptogenesis has been studied within the context of these SU(2) models [45][46][47]; however, these works focused on the UV modes and suffer from similar criticisms regarding regularization and renormalization as the original proposal.…”
Section: Gravitational Leptogenesismentioning
confidence: 99%
“…A natural option of the above modifications, is to include vector fields in the inflationary dynamics, because they naturally could be responsible of several interesting possibilities such as breaking of statistical isotropy, parity violating patterns, the origin of primordial magnetic fields, or even support an inflationary period, among others 1 (see for instance [27][28][29] and references therein). These new features are usually confronted with observations because they can become in an interesting discriminating tests of the proposed models [23,24,30,31].…”
Section: Introductionmentioning
confidence: 99%